IMIGRASI JEPANG KE BRASIL SEBAGAI BAGIAN DARI EKSPANSI EKONOMI JEPANG SEBELUM PERANG DUNIA II - Erni Puspitasari; Indun Roosiani (Media Bahasa, Sastra, dan Budaya Wahana, 2022)
Abstract In the Meiji era until the beginning of Showa, Japan was faced with problems of poverty, population growth and industrialization problems. In order to overcome this, Japan carried out immigration policies for its citizen and efforts to carry out economic expansion to Brazil as a consequence of new industrialized country. The purpose of this research was to analyze the background of the immigration of Japanese citizen to Brazil, as well as various policies implemented as a form of economic expansion efforts in Brazil. The method used in this research was descriptive qualitative. The results showed that although Japan turned into a new industrialized country, it was not accompanied by increasing of welfare, Japan was faced with the problem of urban and rural poverty. In addition, Japan was also faced with population growth, so that the level of competition in finding jobs was high, which results in increased unemployment.  Facing  this  kind  of  situation,  the private sector  with  the support  of  the government had implemented immigration policies for its citizens to Brazil. Through immigration, the Japanese private sector and government carried out economic expansion in order to fulfill raw materials, as well as the distribution of industrial products, through the establishment of colonies, purchase of land for settlements and plantations, economic missions, banking businesses and the establishment of various industries. Keywords: Economic expansion Immigration Japan-Brazil   Abstrak Pada era Meiji hingga awal Showa, Jepang dihadapkan pada masalah kemiskinan, pertambahan penduduk dan masalah industrialisasi. Guna mengatasi hal ini Jepang melakukan kebijakan imigrasi bagi penduduknya dan usaha untuk melakukan ekspansi ekonomi ke Brasil sebagai konsekwensi negara industri  baru.  Tujuan  penelitian  ini  adalah untuk menganalisis  latar belakang terjadinya imigrasi penduduk Jepang ke Brasil, serta berbagai kebijakan yang dilakukan sebagai wujud dari upaya ekspansi ekonomi di Brasil.   Metode yang digunakan dalam penelitian ini adalah deskriptif kualitaif. Hasil penelitian menunjukan bahwa walaupun Jepang berubah menjadi negara industri baru, tetapi tidak disertai dengan peningkatan kesejahteraan, Jepang dihadapkan kepada masalah kemiskinan perkotaan, dan pedesaan. Selain itu Jepang juga dihadapkan kepada pertambahan penduduk, sehingga tingkat kompetisi dalam mencari pekerjaanmenjadi tinggi, yang berakibat meningkatnya  pengangguran. Menghadapi hal seperti ini, pihak swasta dengan dukungan pemerintah melakukan kebijakan imigrasi bagi penduduknya ke Brasil. Melalui imigrasi, pihak swasta dan pemerintah Jepang melakukan ekspansi ekonomi guna pemenuhan bahan baku, serta pendistribusian hasil industri, melalui pendirian koloni, pembelian lahan untuk pemukiman dan perkebunan, misi ekonomi, usaha perbankan dan pendirian berbagai industri. Kata kunci : Imigrasi, ekspansi ekonomi, Jepang, Brasil